Traumatic extradural lumbar haematoma due to a pathological metastatic vertebral body fracture L3 - Daniel Balasa; Gabriela Butoi; Radu Baz; Anca Hancu (Romanian Neurosurgery, 2016)
Spinal epidural haematoma (SEH) is a rare entity. We present the case of a 45 years old patient with lumbar epidural hematoma produced by a L3 vertebral tumoral (metastatic) fracture. Neurological status: cauda equina syndrome with sphincterian deficits, incomplete paraplegia (Frankel C), with neurological level L1. Emergency surgery was performed (L3-L2-bilateral laminectomy, L1 left laminectomy, posterior stabilization L2-L4 by titan screws) offering the possibility to progressive motor, sensitive and sphincterian deficites recovery. Abbreviations: Computer Tomography -CT, Magnetic resonance Imaging-MRI, Spinal epidural haematoma-SEH, Visual analogue scale of pain-VAS. Conclusion: We present a patient with a compressive subacute extradural haematoma, due to a traumatic fracture on a vertebral metastatic tumor who produced cauda equina syndrome. Surgical emergency intervention was mandatory for a good neurological outcome.